1988
DOI: 10.1007/bf00047755
|View full text |Cite
|
Sign up to set email alerts
|

Human tumor xenografts as model for drug testing

Abstract: This paper reviews the history of xenografts, the endpoints commonly used to evaluate response and chemotherapeutic results obtained with serially maintained human tumor xenografts from different laboratories, and discusses the potential clinical relevance of the heterotransplant model for cancer chemotherapy. Specifically, an attempt is made to correlate the published xenograft data with the clinical data. Drug testing with different types of xenotransplanted tumors has shown that the response of xenografts o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(40 citation statements)
references
References 83 publications
1
39
0
Order By: Relevance
“…84 Many studies have indicated that there is a correlation between xenograft chemosensitivity and the sensitivity of the parental patient's tumor. 85 This has been reported for many clinically active drugs. Most authors who have investigated hormonal pretreatment and effectiveness of cytotoxic therapy have simultaneously treated the tumors with GC and anticancer drugs (Table 5).…”
Section: Effect Of Hormonal Pretreatment On the Effectiveness Of Cytomentioning
confidence: 65%
See 1 more Smart Citation
“…84 Many studies have indicated that there is a correlation between xenograft chemosensitivity and the sensitivity of the parental patient's tumor. 85 This has been reported for many clinically active drugs. Most authors who have investigated hormonal pretreatment and effectiveness of cytotoxic therapy have simultaneously treated the tumors with GC and anticancer drugs (Table 5).…”
Section: Effect Of Hormonal Pretreatment On the Effectiveness Of Cytomentioning
confidence: 65%
“…From these studies it seems that cortisone depending on the dose, has a general inhibitory action that is slight and temporary on transplantable tumors of the lymphoid series and no action on transplantable tumors of an epithelial origin. The action of cortisone on the 110 +additive-adrenal-steroidmetastases in lung, liver, treated (85) heart, brain and spleen…”
Section: Effect Of Hormonal Therapy On the Spreading Of Metastasesmentioning
confidence: 99%
“…Patient-derived xenograft (PDX) models are an improvement because they more accurately model the complexity of patient tumor biology (69,70). Limitations of this approach are that each PDX model represents the tumor biology of a single patient, not all biopsies can be engrafted, the host immune system is compromised, and the tumors loose heterogeneity upon engraftment (55,71,72). Genetically engineered mouse models and other syngeneic models are necessary to evaluate a therapy in a system with an intact immune system, but these models rely on murine physiology and form tumors stochastically.…”
Section: Methods Of Detecting Mechanisms Of Response and Resistancementioning
confidence: 99%
“…42 Currently, subcutaneous PDX models, wherein tumor cells are transplanted underneath the skin of the hindquarters or in the mammary fat pad dominate the field of primary xenografts, succeeding intra-ocular, embryonic, and athymic systems. 29,61 Many groups also transplant cells under the kidney capsule or orthotopically; the latter of which may better replicate the tumor microenvironment than subcutaneous models, and thus may be most physiologically relevant. Regardless of the transplantation site, the cellular complexity and architecture of PDX tumor models remains remarkably faithful to the tumor in its natural state in most cases-complete with invading vasculature and supporting stromal cells (Figure 1d).…”
Section: Pdxs: Models For the 21st Centurymentioning
confidence: 99%
“…For example, breast cancer PDX models appear to be particularly difficult to establish, with a 27% engraftment rate in the most successful laboratories, compared with ovarian (65%), lung (50%), melanoma (59%), and colorectal (68%) cancer. 51,61 Mounting evidence suggests that the exact mouse strain (eg, NOD/SCID vs NSG) does not significantly impact engraftment efficiency of most solid tumor types, but strain differences can impact the rate at which tumors arise. 29,64,65 PDX tumor models can be propagated as either discrete tumor fragments or as single-cell suspensions.…”
Section: Pdxs: Models For the 21st Centurymentioning
confidence: 99%